A Road Through Pakistan, and What This Means for India. Issue 3 (4th May 2019) - Zaidi, S. Akbar
ABSTRACT: Pakistan's largest donor has been the United States of America, granting around 70 bn in aid. In 2015, China, as part of its One Belt One Road global ambitions, promised Pakistan 46 bn (since revised to 60 bn), for a road running from its border to the port of Gwadar. The China Pakistan Economic Corridor (CPEC), is being seen as a 'fate-changer' for Pakistan. CPEC could change Pakistan's fate in more ways than one; this article explores the domestic and regional consequences of China's involvement in Pakistan, and what this will mean for South Asia and for India.